Pemanfaatan Sampah Plastik Sebagai Keterampilan Siswa Untuk Pembuatan Ecobrick Di Desa Ngingit Kecamatan Tumpang Kabupaten Malang - Tahilia, Yohanes Laba; Yazidah, Nok Izatul; Sulistyorini, Yunis; Riyanto, Riyanto; Saputra, Nisvu Nanda (Community Services and Social Work Bulletin, 2025)
This community-based service initiative explores an educational and environmental intervention conducted in Alas Gede, Ngingit Village, Tumpang District, Indonesia, focusing on the transformation of plastic waste into ecobricks by elementary school students. As plastic pollution escalates into a critical global environmental challenge, this program presents an integrative solution by combining environmental education with practical waste management skills. Ecobricks—plastic bottles densely packed with clean, non-organic waste—serve as a low-cost, scalable, and ecologically responsible alternative for repurposing plastic waste into usable construction materials. The uniqueness of this initiative lies in its pedagogical approach that merges hands-on learning, environmental awareness, and community empowerment at the grassroots level. The program not only enhances students’ cognitive and behavioral competencies regarding recycling practices but also strengthens collective environmental stewardship within the village. This article delineates the step-by-step implementation of the program, identifies operational challenges, and evaluates its multi-dimensional impacts on both the educational environment and the broader community. Findings suggest that integrating ecobrick production into school-based environmental curricula fosters sustainable behavior, promotes participatory waste management, and has potential for replication in other rural contexts facing similar ecological issues